2022
DOI: 10.1021/acsnano.2c01206
|View full text |Cite
|
Sign up to set email alerts
|

Cationization-Enhanced Type I and Type II ROS Generation for Photodynamic Treatment of Drug-Resistant Bacteria

Abstract: Photodynamic therapy as an emerging phototheranostic approach holds great potential for antibacterial treatment, but is limited by compromised reactive oxygen species (ROS) generation in an aggregate and hypoxic microenvironment. Herein, we report a molecular cationization approach to boost the ROS, especially type I ROS generation of aggregationinduced emission (AIE) photosensitizers for photodynamic treatment of drugresistant bacteria. Such cationization reinforces the electron-accepting ability of the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 50 publications
2
86
0
Order By: Relevance
“…The highly efficient generation of Type I ROS and excellent photothermal conversion ability are resourcefully integrated into these PQ-cored PSs to achieve Type I photodynamic and photothermal combined antitumor treatment. Other detailed studies on the photophysical and photochemical mechanisms of AIE-PSs provided a reference for the molecular design of AIE-PSs basing on the Type I mechanism [ 86 89 ].
Fig.
…”
Section: Design Of Aie-pss For Pdtmentioning
confidence: 99%
“…The highly efficient generation of Type I ROS and excellent photothermal conversion ability are resourcefully integrated into these PQ-cored PSs to achieve Type I photodynamic and photothermal combined antitumor treatment. Other detailed studies on the photophysical and photochemical mechanisms of AIE-PSs provided a reference for the molecular design of AIE-PSs basing on the Type I mechanism [ 86 89 ].
Fig.
…”
Section: Design Of Aie-pss For Pdtmentioning
confidence: 99%
“…To date, diverse subcellular organelle-targeted type I AIE PSs-based anti-tumor systems have been exploited in succession [ 57 ]. For instance, Feng et al [ 58 ] developed a class of cationic AIE PSs possessing a specific tumor cell mitochondrial targeting feature to facilitate both type I and type II PDT. Zhao et al [ 48 ] reported two type I AIE PSs to obtain selective accumulation in the ER and effectively arouse ER-stress-mediated cell apoptosis and autophagy upon PDT, by producing highly oxidizing type I radicals under light illumination.…”
Section: Applications Of Type I Aie Pssmentioning
confidence: 99%
“…26,[49][50][51] So, for general antibacterial methods based on AIEgens, the regular irradiation and dressing change are usually required. [52][53][54] As for the proposed anti-biofilm method based on AIEzymes (Figure 7a), the irradiation and the dressing change are not required, avoiding the frequent operations and the exogenous infection. Because the DNase-like activity of AIEzymes can continuously catalyze the hydrolyzation of eDNA in EPS without irradiation, AIEzymes can eliminate recurrence of biofilms and realize persistent anti-infection.…”
Section: In Vivo Antibacterial Therapy and Wound Healingmentioning
confidence: 99%